The sanatorium : a novel - Pearse, Sarah (New York : Pamela Dorman Books/Viking, 2021)
"A chilling debut in which a detective must uncover the dark history of a luxury hotel in the Alps if she has any hope of stopping the deaths that won't let up. . . Half-hidden by forest and overshadowed by threatening peaks, Le Sommet has always been a sinister place. Once a sanatorium treating tuberculosis patients, it was abandoned years ago and had fallen into disrepair. Long plagued by troubling rumours, it has recently been renovated into a lavish hotel. And an imposing, isolated hotel, high up in the Swiss Alps, is the last place detective Elin Warner wants to be. But having received an invitation out of the blue to celebrate her estranged brother's recent engagement, she had no choice but to accept. Arriving in the midst of a threatening storm, Elin is immediately on edge. Though it's a stunning retreat, something about the hotel makes her nervous - as does her brother, Isaac. When Elin wakes the following the morning to discover Isaac's fiancee Laure has vanished without a trace, Elin's alarm grows. With the storm cutting off access to and from the hotel, the more the remaining guests start to panic. Yet no one has realized that another woman has gone missing. And she's the only one who could have warned them just how much danger they're all in . . "--
Keywords: Hotels -- Switzerland -- Fiction; Missing persons -- Fiction; Hotels, motels, etc. -- Switzerland -- Fiction